Seawater intrusion decreases the metal toxicity but increases the ecological risk and degree of treatment for coastal groundwater: An Indian perspective. (1st October 2022) - Bhagat, Chandrashekhar; Kumar, Manish; Mahlknecht, Jürgen; Hdeib, Rouya; Mohapatra, Pranab Kumar
Abstract: Contaminant vulnerability in the critical zones like groundwater (GW)-seawater (SW) continuum along the entire Gujarat coast was investigated for the first time through an extensive water monitoring survey. The prime focus of the study was to evaluate whether or not: i) seawater intrusion induced metal load translates to toxicity; ii) in the coastal groundwater, metal distribution follows the pattern of other geogenic and anthropogenic contaminants like NO3 - and F-; and iii) what future lies ahead pertaining to metal fate in association with saturation conditions of the coastal aquifers. The spatial distribution of contaminants depicts that the Gulf of Khambhat area is highly contaminated. Ecological risk assessment (ERA) indicates that the Gujarat coast is experiencing a high ecological risk compared to the southeast coast of India. Investigation results revealed that metals, pH, NO3, and CO3 are more vulnerable at the SW-GW mixing interface. An increase in pH is reflected in fewer ionic species of metals in the GW. Salinity ingress due to seawater intrusion (SWI) reduces the toxicities of all trace metals except Cu, attributed to the increase of Ca in GW, leading to dissociation of CuCO3 . Reactive species are dominant for Zn and Cd; and M-CO3 ligands are dominant for Cu and Pb owing to the undersaturation of dolomite and calcite in the aquifer system. SWI tends to increase the metal load but the toxicity of metals varies with the density of industries, anthropogenic activities, changes in the mixing-induced saturation conditions, and intensive salt production across the coast. Multivariate analysis confirmed that the hydrogeochemical processes change due to GW-SW mixing and dictates over natural weathering. The ecological risk index (ERI) for the Arabian sea is experiencing moderate (300 ≥ ERI>150) to high ecological risk (ERI >600). Children population is likely to encounter a high health risk through ingestion and dermal exposure than adults. Overall, the study emphasizes the complexity of toxicity-related health impacts on coastal communities and suggests the dire need for frequent water monitoring along the coastal areas for quick realization of sustainable development goals. Graphical abstract: Image 1 Highlights: Seawater intrusion increases metal load but does not necessarily translate to toxicity. In the coastal groundwater, metal distribution differs the pattern of NO3 − and F − . M 2+ and CO3 2− forms were dominant for Zn & Cd; and Cu & Pb, respectively. Higher intrusion seems to decrease free ionic metals but has no profound effect on pH. Undersaturation of Dolomite & Calcite reasons the dominance of MCO3 forms. Abstract : Capsule: Seawater intrusion increases metal load but does not necessarily translate to toxicity.